1976
DOI: 10.2307/3225137
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Behavior and Feeding Mechanisms of the Suctorian Heliophrya erhardi (Rieder) Matthes Preying on Paramecium

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…When a tentacle touches a possible prey, the discharge of haptocysts is able to penetrate the prey's membrane, forming a connection between the predator and the prey and injecting the extrusome content into the latter, which also concurs to the fusion of the membranes belonging to the two organisms [13,34]. However, the fusion of the two membranes is not always immediate, for example, in Heliophrya erhardi, Spoon et al [35] observed that many specimens of Paramecium contacting the tentacles of the suctorian escaped discharging trichocysts at the point of contact, suggesting that Paramecium is able to defend itself from the puncture of the haptocysts.…”
Section: The Peculiar Tentacles Of Suctoriansmentioning
confidence: 99%
“…When a tentacle touches a possible prey, the discharge of haptocysts is able to penetrate the prey's membrane, forming a connection between the predator and the prey and injecting the extrusome content into the latter, which also concurs to the fusion of the membranes belonging to the two organisms [13,34]. However, the fusion of the two membranes is not always immediate, for example, in Heliophrya erhardi, Spoon et al [35] observed that many specimens of Paramecium contacting the tentacles of the suctorian escaped discharging trichocysts at the point of contact, suggesting that Paramecium is able to defend itself from the puncture of the haptocysts.…”
Section: The Peculiar Tentacles Of Suctoriansmentioning
confidence: 99%
“…( 2 ) Feeding Increases in output of the contractile vacuole complex occur when some protozoa feed (MacLennan, 1933; Frisch, 1937; Rudzinska & Chambers, 1951 ;Kitching, 1951,195zb; Spoon, Chapman, Cheng & Zane, 1976;Canella & Rocchi-Canella, 1976). This is presumably due to the diffusion of water from food vacuoles into the cytoplasm.…”
Section: Suggested Functions Of Contractile Vacuole Complexes ( Imentioning
confidence: 99%
“…This well-known species has been reported several times in the half century since the original description. Most of these reports, however, focused on the ultrastructure of the tentacles, rather than attempting to present accurate morphological data and taxonomic research ( Hauser and Eys, 1976 ; Spoon et al, 1976 ; Hanke-Bücker et al, 2000 ). There is therefore a need to provide an improved diagnosis here.…”
Section: Resultsmentioning
confidence: 99%